Financial Ratios and Tax Awareness of Indonesian Companies - Syafii Syafii; Aliffianti Safiria Ayu Ditta; Dien Ajeng Fauziah; Khoirul Abidin (Accounting Study Programme Faculty of Economics and Business Universitas Negeri Surabaya, 2026)
Introduction/Main Objectives: This study examines the relationship between corporate financial ratios and tax awareness, emphasizing nationalism. Background Problems: The paper addresses the issue of corporate tax awareness and its impact on tax compliance. The central research question is: